The Analytical Study of Vibhajjavãda in DheravadaBuddhisphilosophy - Chumsen, Chatree (Mahachula Academic Journal, 2018)
This paper has an attempt to analyze the view of digestion (Vibhajjavãda) in Theravada Buddhist philosophy. The view of digestion (Vibhajjavãda) of Theravada Buddhist philosophy has been adapted as the way of thinking aiming at adding several points of problems in order to see and understand the truth, or to be in accordance with the truth. The view of digestion is regarded as the essence of Buddhist philosophy, as the method for answering problems, and as the way of thinking that could help ones to see the ethical value of both general principle of Buddhist Philosophy, and the way that enable ones to reach the ultimate goal, viz., detachment. Besides, it is the method for evaluation of the Buddha’s philosophy